Stories That Matter: Unveiling the Experiences of Students in Writing Research Papers at Bambad National High School - GARDE, SHARMAINE SHEENE; MANGINDRA, ANESA (International Journal of Arts, Sciences and Education, 2025)
The aim of this research is to determine the experiences of students in writing research papers at Bambad National High School, Isulan, Sultan Kudarat, for the academic year 2024-2025. The researcher employed a qualitative research design, specifically transcendental phenomenology, to explore and understand students' perspectives on conducting research papers. A thorough examination was conducted on twelve Grade 12 students enrolled in the research subject. Data was gathered through in-depth interviews, which allowed for a deeper understanding of the challenges they faced, their opinions, and the benefits they gained from writing research papers. Thematic analysis in phenomenology was used in the data analysis process, consisting of six main steps: familiarization with the data, initial coding and theme development, identifying themes, analyzing themes, defining and naming themes, and reporting findings, following Moustakas' (1994) model.Writing a research paper is a significant experience for Grade 12 students, greatly affecting their emotions, cognition, and physical well-being. It brings joy and a sense of accomplishment but also induces stress, frustration, and mental breakdowns due to the challenges involved in the process. From the students' perspective, research writing is a step toward their professional development, especially for those aspiring to become experts in this field. They see it as a means to help their families and communities.To improve their research writing experience, it is suggested that teaching methods be clarified, appropriate strategies be employed, and teachers develop greater patience to ease the learning process. Overall, research writing is a challenging but essential part for students' academic lives. Despite its difficulties, it provides numerous opportunities for personal and professional growth, especially with adequate guidance and support from teachers.